2014
DOI: 10.1177/1358863x14557152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of cerebral angiography in the preoperative assessment of endocarditis

Abstract: Cerebral angiography is an invasive procedure utilized without supporting guidelines in preoperative evaluations of infective endocarditis (IE). It is used to identify mycotic intracranial aneurysm, which is suspected to increase the risk of intracranial bleeding during cardiac surgery. Our objectives were to: (1) assess the utility of cerebral angiography by determining which subset of IE patients benefit from its performance; and (2) identify clinical and noninvasive screening tests that can preclude the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
12
2
Order By: Relevance
“…A prior study of IIA with DSA found that the absence of focal neurological deficit or encephalopathy conveyed high NPV and the absence of acute intracranial hemorrhage also had a high NPV for the presence of IIA [16]. However, in our cohort, the NPVs, sensitivity, and specificity were lower for those variables.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…A prior study of IIA with DSA found that the absence of focal neurological deficit or encephalopathy conveyed high NPV and the absence of acute intracranial hemorrhage also had a high NPV for the presence of IIA [16]. However, in our cohort, the NPVs, sensitivity, and specificity were lower for those variables.…”
Section: Discussioncontrasting
confidence: 50%
“…The frequency of IIAs who underwent DSA (17.6%) in our cohort is higher than previously reported (5-9%) [6,16]; this is likely due to selection bias because our cohort consists of patients with acute/subacute focal neurological presentation or abnormal cerebral imaging. Therefore, true prevalence of IIA among persons with IE is likely far lower than that indicated in our report.…”
Section: Discussioncontrasting
confidence: 50%
“…Patients with documented ischemic stroke, asymptomatic cerebral septic emboli, or neurological findings suggestive of stroke should undergo additional imaging, if possible, including MRI with and without gadolinium, for further diagnosis and risk stratification Cerebral angiography should be reserved for patients with evidence of hemorrhage on noninvasive imaging, focal neurologic deficits, or altered mental status Surgery for IE is associated with higher risk of neurological complications than valve surgery in non‐IE patients including hemorrhagic transformation of ischemic strokes and new ischemic or hemorrhagic lesions …”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…CT and MRI are thought to be poorly sensitive in identifying mycotic aneurysms and for that reason cerebral angiography has been employed. An analysis of 151 patients with IE undergoing cerebral angiography demonstrated that noninvasive imaging, particularly the absence of intracranial bleed on MRI, conveyed a negative predictive value (NPV) of 0.977 (95% confidence interval [CI] 0.879‐0.996) for the presence of mycotic aneurysm . Absence of focal neurologic deficit or altered mental status were found to convey a NPV of 0.990 (95% CI 0.945‐0.998) and 0.944 (95% CI 0.883‐0.974), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In patients who presented with hemorrhage, 14 of 63 (22.2%) harbored an MA. In a similar study, Monteleone et al 6 identified MA in 7 of 151 (4.6%) patients who underwent cerebral angiography. Only one MA >3 mm was identified by noninvasive imaging (sensitivity, 0.17).…”
Section: Dynamic Angiographic Changes Of Mycotic Aneurysms E9mentioning
confidence: 94%